Talent Management through «Trainee Programmes» Conceptual Preliminaries and Research-Based Advice on The Design of Corporate Educational Programmes for University Graduates - Thom, Norbert (The Arab Journal of Administration, 2019)
Studies suggest that HR managers worldwide perceive talent management as a field of managerial activity that is of crucial importance, but rather badly handled in actual practice. So-called «trainee» or «graduate programmes» – on-the-job training programmes for university graduates – offer an excellent path towards improvement here, but so far have received surprisingly scant attention outside German-speaking Europe. Drawing on many years of research and close relations with HR practitioners, the author hopes with the present paper to stimulate an interest in such programmes among HR specialists in Poland and, as the case may be, further regions of Eastern Europe, and to provide an overview of the essential dos and don’ts in implementing them.